PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN PADA PT ELANG TRANSPORTASI INDONESIA DI JAKARTA - Euis Siti Komalasari; Widiyono Widiyono; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine how much influence the Compensation and Organizational Culture have on Turnover Intention of PT. Elang Transportation Indonesia in Jakarta.The method used in this study is a Quantitative method, this study population is PT. Elang Transportation Indonesia employees, amounting to 57 respondents, each respondents was given to 48 statements using a Likert Scale and data analysis techniques using validity, reliability, multiple linear regression analysis.The hypothesis test using the T test and F test and coefficient of determination. The result showed that the effect of Compensation (X1) partially on Turnover Intention Employees (Y), was 34.2%, the influence of Organizational Culture partially on Turnover Intention Employees was 6.9% and simultaneously Compensation (X1) and Organizational Culture (X2) towards Turnover Intention Employees (Y) PT. Elang Transportation Indonesia in Jakarta is 36.9%, while the remaining 63.1% is influence by other factors.The researcher suggest that we need to Collect Labor Agreement in order to know the right and the obligation of both employee and company.Organizational culture carried out with good norms and ethics also aims to create a conducive atmosphere and the creation of a solid team engagement among fellow employees in order to create comfort work environment so that it can contribute more to the employees’ turnover.